Development of a continuous flow synthesis of FGIN-1-27 enabled by in-line 19F NMR analyses and optimization algorithms. Issue 10 (9th August 2021) - Vasudevan, N.; Aka, Ehu C.; Barré, Elvina; Wimmer, Eric; Cortés-Borda, Daniel; Giraudeau, Patrick; Farjon, Jonathan; Rodriguez-Zubiri, Mireia; Felpin, François-Xavier
Abstract : A continuous flow synthesis of FGIN-1-27 has been developed using enabling technologies such as real-time in-line benchtop 19 F NMR analysis and an optimization algorithm. Abstract : A straightforward continuous flow synthesis of FGIN-1-27, a compound with potent anxiolytic effects, is described from inexpensive and commercially available starting materials. The four-step synthesis includes the direct C–H arylation of an indole with an arenediazonium salt. The continuous flow route was developed thanks to the use of enabling technologies such as real-time in-line benchtop 19 F NMR analysis and an optimization algorithm assisting the decision-making process. These enabling technologies increase the process safety and minimize the number of experiments required in optimization campaigns.